2023
DOI: 10.1002/ana.26657
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography with [18F]‐DPA‐714 Unveils a Smoldering Component in Most Multiple Sclerosis Lesions which Drives Disease Progression

Abstract: Objective: To determine the prognostic value of persisting neuroinflammation in multiple sclerosis (MS) lesions, we developed a 18 kDa-translocator-protein-positron emission tomography (PET) -based classification of each lesion according to innate immune cell content and localization. We assessed the respective predictive value of lesion phenotype and diffuse inflammation on atrophy and disability progression over 2 years. Methods: Thirty-six people with MS (disease duration 9 AE 6 years; 12 with relapsing-rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Supporting this hypothesis, their enlargement was shown to predict the slow expansion of chronic active periventricular lesions on MRI [56 ▪▪ ]. On TSPO-PET, a similar correlation was found between ChP enlargement and the percentage of chronic MS lesions containing a smoldering inflammatory component, the strength of the association being higher in periventricular white matter [57 ▪ ]. Finally, our group recently reported that greater ChP size was associated with lower periventricular remyelination ( r = −0.79, P = 0.0018) in two independent cohorts of PwMS [55 ▪ ].…”
Section: The Imaging Signature Of Choroid Plexuses In Multiple Sclero...supporting
confidence: 52%
“…Supporting this hypothesis, their enlargement was shown to predict the slow expansion of chronic active periventricular lesions on MRI [56 ▪▪ ]. On TSPO-PET, a similar correlation was found between ChP enlargement and the percentage of chronic MS lesions containing a smoldering inflammatory component, the strength of the association being higher in periventricular white matter [57 ▪ ]. Finally, our group recently reported that greater ChP size was associated with lower periventricular remyelination ( r = −0.79, P = 0.0018) in two independent cohorts of PwMS [55 ▪ ].…”
Section: The Imaging Signature Of Choroid Plexuses In Multiple Sclero...supporting
confidence: 52%
“…Beside targeting both adaptive and innate peripheral immune responses, the CNS penetrance and effect on both B cells and microglia/macrophages suggest that BTKi can be an attractive approach to treat low-level inflammation in smouldering MS. Activation and functional change of microglia in the normalappearing white matter (NAWM) and in the rim of chronic active lesions participate in propagation of chronic tissue damage and maintaining such low-level chronic inflammation in concert with astrocytes, B and T lymphocytes (20)(21)(22). Microglia activation in the NAWM can be visualized by PET, while chronic active lesions are reflected on MRI as slowly evolving (SEL) and paramagnetic rim lesions (PRLs) (14,(23)(24)(25). Chronic active lesions as PRLs are already present in the early stage of MS and associate with progressive MS and advanced clinical disability (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…In multiple sclerosis (MS), chronic active, slowly expanding, smouldering lesions characterized by the accumulation of myeloid cells at the lesion edge are associated with brain atrophy and predict the accumulation of irreversible disability, which in turn drives disease progression 4 6 . In these lesions, persistently activated myeloid cells are a continuous source of neurotoxic factors, including tumour necrosis factor (TNF), interleukin-1β (IL-1β), nitric oxide (NO) and reactive oxygen species (ROS), causing remyelination failure and secondary neuronal/axonal damage 7 .…”
Section: Mainmentioning
confidence: 99%